Analysist Web-Based of Laundry Information System - Devi, Indah Cyithia; Zhafirah, Farah Hana; Farian, Rida Indah (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Laundry is business engaged in services that are now commonly found. The high demand for laundry services makes laundry owners in Sungai Bambu, North Jakarta look for ways to keep transaction records neatly organized and not lose records or damage that is often experienced by customers or owners. In addition, employees must calculate the total price of the weight of the items to be washed, so that it takes a long time. Laundry also provides a variety of laundry services that can be added at any time. Besides making manual reports. To overcome this, laundry service information system is designed using the waterfall method built with Visual Studio as an interface and SQL Server as data storage. Design of this information system will make it easy to collect transaction data and minimize data loss or damage, generate automatic reports, and can perform special laundry services.